Evaluation of acute physiology and chronic health evaluation IV predictive scoring as mortality predictor among individual with cholangitis - Yusuf, Muhammad; Usman, Nurhayat; Rudiman, Reno; Hutagalung, Muhammad Bayu Z. (International Journal of Research in Medical Sciences, 2018)
Background: Evaluation of the effectiveness of care and clinical outcomes in critically ill patients is dependent on predictive scoring models that calculate measures of disease severity and mortality. Cholangitis is an infection and obstruction of the biliary system. The APACHE IV scoring system is a logistic regression model incorporating physiologic and laboratory parameters. APACHE IV is the most updated scoring system for Intensive Care Unit (ICU) mortality prediction. Methods: A cohort study with 65 cholangitis patient that fulfilled diagnostic criteria of Tokyo guideline 2013 was included. The APACHE IV score was assessed during first day admission to ICU. APACHE IV score and predicted mortality rate was calculated and evaluated using the area under the ROC curve (AUROC). Results: Overall in-hospital mortality was 26.2 %. The APACHE IV score mean was 76.7 with the highest score was 133 point. AUROC of the APACHE IV score was 0.97 with the cut point of 0.87, 95% CI (0.94, 0.91) indicating good performance in this cohort. Conclusions: APACHE IV scoring system has good discrimination in the prediction of mortality models for cholangitis patients.